Relacionando características de clusters ao desenvolvimento de capacidades organizacionais para sustentabilidade: proposta e análise de um framework - Bezerra, Maria Clara da Cunha (2019)
Sustainability is a worldwide theme and has led companies, stakeholders and all levels of society to seek ways to achieve it. Following that, this paper relates sustainability with two other research themes, which have been vaguely addressed together until now, which are the organizational capabilities and the industrial clusters. The literature agrees that the development of organizational capacities can influence the sustainability of companies. On the other hand, the literature also argues that industrial clusters play an important role in the development of company‟s organizational capabilities, since they represent a business environment outside of them, which plays a vital role in their performance. Clusters can also play an important role in the sustainability of companies, since clusters can offer benefits on sustainable issues. Although previous indications in the literature regarding the relationship between these three constructs (corporate sustainability, organizational capabilities and industrial clusters), this interconnection still requires further research. Therefore, organizational capabilities for sustainability (OCS) were identified from literature and organized into seven categories: capabilities linked to collaborative relationships for sustainability (OCS1); capabilities linked to the absorption of knowledge / learning about sustainability (OCS2); capabilities linked to sustainable innovation / technology (OCS3); skills linked to alignment / motivation for sustainability (OCS4); capabilities linked to marketing and external communication for sustainability (OCS5); flexibility / adaptation capabilities for sustainable issues (OCS6) and capabilities linked to sustainable operations management (OCS7). The analysis of literature also allowed to identify five characteristics of companies inserted clusters: geographical proximity of the companies (industrial agglomeration); interactions / associations in formal and informal networks at the local level between firms for collaboration; associations / interactions with support institutions (public and private companies); stimulus to competition character/ sociocultural factors. From this, a theoretical framework was developed. This framework proposes relations between the characteristics of companies inserted in clusters and the organizational capabilities for sustainability, through the benefits for the companies coming from these characteristics of the clusters. This theoretical framework was applied through case studies in companies inserted in Brazilian footwear‟s cluster. It was evidenced 16 of the 29 relationships that had been proposed in theoretical framework and from these relations, were developed propositions that led to the refinement of initially proposed framework. Finally, as a major contribution, this study advances in literature by providing empirical evidence of the crucial role that clusters can play in enabling companies to develop COS and thus improve their corporate sustainability.